PENERAPAN METODE HEURISTIK (ALGORITMA IDA* DAN B&B) DALAM PEMECAHAN N-Queen Problem - Novi Penna; Sebastianus Adi Santoso Mola; Meiton Boru (Universitas Nusa Cendana, 2018)
N-Queen problem is a problem which a N-Queen pawn in is place chess with n x n size. N-Queen pawn is a put in such away in chess board with under condition that the queen pawns do not attack each other. The attacking movement of N-Queen problem is similar to the way of the queen pawn attacking in chess. Commonly the queen pawn moves horizontally to left and right, forward and backward vertically and also diagonally, so there are no queen pawns in a line of horizontal, vertical and diagonal.Heuristical searching is one of the method which can be used to solve the game of N-Queen problem selectively, by giving solution of the shortest time channel efficiently in order to able the user to solve this game well, fast and relevantly. Some algorithms that use heuristic is Iterative Deepening algorithm A* (IDA*) and Branch and Bound (B&B) algorithm. The used heuristic function is by seeing the numbers of boxes which are empty and the number of queen which is not be put in board yet.The aim of making this final project to implement the solving of N-Queen problem using heuristic searching (B&B and IDA*). From this implementation could be seen that IDA* and B&B algorithm is able to give channel in solving N- Queen problem. After a repetition of test by using 19 sheet of data, it is shown the comparison of result between IDA* algorithm and B&B algorithm which IDA* algorithm result the shorter channel in solving N-Queen problem based on the node 61%, and time 41% which better than B&B algorithm.